Expansion of the molecular and morphological diversity of Acanthamoebidae (Centramoebida, Amoebozoa) and identification of a novel life cycle type within the group. Issue 1 (December 2016) - Tice, Alexander; Shadwick, Lora; Fiore-Donno, Anna; Geisen, Stefan; Kang, Seungho; Schuler, Gabriel; Spiegel, Frederick; Wilkinson, Katherine; Bonkowski, Michael; Dumack, Kenneth; Lahr, Daniel; Voelcker, Eckhard; et al.
Abstract Background Acanthamoebidae is a "family" level amoebozoan group composed of the generaAcanthamoeba, Protacanthamoeba, and very recentlyLuapeleamoeba . This clade of amoebozoans has received considerable attention from the broader scientific community asAcanthamoeba spp. represent both model organisms and human pathogens. While the classical composition of the group (Acanthamoeba + Protacanthamoeba ) has been well accepted due to the morphological and ultrastructural similarities of its members, the Acanthamoebidae has never been highly statistically supported in single gene phylogenetic reconstructions of Amoebozoa either by maximum likelihood (ML) or Bayesian analyses. Results Here we show using a phylogenomic approach that the Acanthamoebidae is a fully supported monophyletic group within Amoebozoa with both ML and Bayesian analyses. We also expand the known range of morphological and life cycle diversity found in the Acanthamoebidae by demonstrating that the amoebozoans "Protostelium "arachisporum, Dracoamoeba jormungandri n. g. n. sp., andVacuolamoeba acanthoformis n.g. n.sp., belong within the group. We also found that "Protostelium "pyriformis is clearly a species ofAcanthamoeba making it the first reported sporocarpic member of the genus, that is, an amoeba that individually forms a walled, dormant propagule elevated by a non-cellular stalk. Our phylogenetic analyses recover a fully supported Acanthamoebidae composed of five genera. Two of these genera (Acanthamoeba andLuapeleameoba ) have members that are sporocarpic. Conclusions Our results provide high statistical support for an Acanthamoebidae that is composed of five distinct genera. This study increases the known morphological diversity of this group and shows that species ofAcanthamoeba can include spore-bearing stages. This further illustrates the widespread nature of spore-bearing stages across the tree of Amoebozoa. Reviewers This article was reviewed by Drs. Eugene Koonin, Purificacion Lopez-Garcia and Sandra Baldauf. Sandra Baldauf was nominated by Purificacion Lopez-Garcia, an Editorial Board member.